A Latent‐Fire‐Detecting Olfactory System Enabled by Ultra‐Fast and Sub‐ppm Ammonia‐Responsive Ti3C2Tx MXene/MoS2 Sensors. (24th August 2022) - You, Cheng‐Wei; Fu, Teng; Li, Chun‐Bo; Song, Xin; Tang, Bo; Song, Xuan; Yang, Yang; Deng, Ze‐Peng; Wang, Yu‐Zhong; Song, Fei
Abstract: Explosive developments in modern society bring huge fire loads. Previous fire detections at early stages are basically enabled by recognizing abnormal high‐temperatures, smoke particles, and flame light signals. However, the identification of these characteristic signals is generally accompanied by an open flame or smoke, which makes it difficult to prevent further serious damage. Herein, a latent‐fire‐detecting strategy of trace ammonia (NH3 ) analysis based on nanohybrid Ti3 C2 Tx MXene/MoS2 is proposed. Benefiting from nanoscale high‐density Schottky heterojunctions between MoS2 and Ti3 C2 Tx MXene, ultrafast (3 s @100 ppm), sub‐ppm (200 ppb minimum), and high‐sensitivity (81.7% @100 ppm and 10.2% @200 ppb) detection of NH3 are enabled. An assembled latent‐fire‐detecting olfactory system (LFOS) based on MXene/MoS2 and interdigital electrodes can monitor trace NH3 releases from different materials (wool, leather, foam, and nylon) during thermal decomposition at latent stages. Notably, the LFOS can detect fire threats at least 84 s earlier than commercialized smoke detectors, providing more fire dealing time and an escape period; this offers a promising latent‐fire‐warning approach for eliminating fire treats at an early stage. Abstract : Inspired by the significant contributions of micro/nanoscale Schottky heterojunctions to enhancing gas‐sensing performances, here, a new assembled latent‐fire‐detecting olfactory system (LFOS) based on Ti3 C2 Tx /MoS2 and interdigital electrodes is developed for recognizing trace NH3 volatiles. The LFOS can detect fire threats at least 84 s earlier than commercialized smoke detectors, significantly increasing the fire dealing time and escape period.